Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1103/physrevlett.111.233004
|View full text |Cite
|
Sign up to set email alerts
|

Vibrationally Resolved Decay Width of Interatomic Coulombic Decay in HeNe

Abstract: We investigate the ionization of HeNe from below the He 1s3p excitation to the He ionization threshold. We observe HeNe+ ions with an enhancement by more than a factor of 60 when the He side couples resonantly to the radiation field. These ions are an experimental proof of a two-center resonant photoionization mechanism predicted by Najjari et al. [Phys. Rev. Lett. 105, 153002 (2010)]. Furthermore, our data provide electronic and vibrational state resolved decay widths of interatomic Coulombic decay in HeNe di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
69
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(78 citation statements)
references
References 30 publications
6
69
2
1
Order By: Relevance
“…For instance, Auger decay5152 or ICD in dimers5355 were shown to take place on femtosecond time-scales. However, in the case of ICD in dimer a virtual photon model predicts a substantial increase of the ICD lifetime for higher excited states27 in accordance with experimental observation54.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…For instance, Auger decay5152 or ICD in dimers5355 were shown to take place on femtosecond time-scales. However, in the case of ICD in dimer a virtual photon model predicts a substantial increase of the ICD lifetime for higher excited states27 in accordance with experimental observation54.…”
Section: Discussionsupporting
confidence: 84%
“…It is probable that in contrast to most of previous studies of correlated electron dynamics91011125152535455 the precursors for observed CED-channels are populated few picoseconds after the absorption of XUV-photons. On this time-scale the clusters are substantially expanded and resemble a strongly diluted plasma2443.…”
Section: Discussionmentioning
confidence: 59%
“…A similar approach to that of Öhrwall et al [18] was recently chosen by Trinter and coworkers [23]. In their experimental work they investigated ICD after resonant excitation of a HeNe mixed cluster [24][25][26][27][28][29][30][31]: a resonant excitation of the He atom caused the Ne atom to be ionized after ICD.…”
Section: Early Theoretical and Experimental Workmentioning
confidence: 95%
“…This two-center ionization channel can be remarkably effective and strongly dominate over the usual direct single-center PI. It was experimentally observed in helium-neon dimers using synchrotron radiation [23].In this communication we study a dynamic variant of resonant two-center PI occurring in slow atomic collisions (see figure 1). The average distance R between colliding atoms is (many) orders of magnitude larger than in a bound system and the probability for the two-center PI scales as R −6 [22].…”
mentioning
confidence: 91%
“…This two-center ionization channel can be remarkably effective and strongly dominate over the usual direct single-center PI. It was experimentally observed in helium-neon dimers using synchrotron radiation [23].…”
mentioning
confidence: 99%